Psychopathology and personality dimensions : the selected works of Gordon Claridge - Claridge, Gordon (London : Routledge, 2018)
"In the World Library of Psychologists series, international experts present career-long collections of what they judge to be their finest pieces extracts from books, key articles, salient research findings, and their major practical theoretical contributions.In this fascinating collection, Professor Gordon Claridge charts the development of a model of mental health that blurs the line between madness and sanity, conditions such as schizophrenia and other forms of psychosis seen as dimensions of normal personality and temperament rather than separate abnormalities. Working with, and influenced by, the late Hans Eysenck, Claridge is celebrated for evolving research on personality and psychological disorders into a revised view of the spectrum of psychotic traits. The concept of schizotypy, re-evaluated by Claridge, sees mental illness not as a pathology suffered by a few, but as the end of a continuum experienced by us all. Psychopathology and Personality Dimensions brings together some of the authors most influential publications on the topics of schizotypy and psychoticism, personality disorders, and the use of drug techniques to investigate normal and abnormal individual differences. Interspersed throughout with specially-written retrospectives by Professor Claridge, looking back at his work and contextualising where it sits in the wider literature, the collection illustrates a radical and influential model of mental illness that continues to resonate today. This book is an essential resource for all those engaged or interested in the field of personality and psychological disorders."--Provided by publisher.
chapter Commentary / Gordon Claridge -- chapter 1 Hans Eysenck$1 (Bs contribution to our understanding of personality and psychological disorders -- s A personal view / Gordon Claridge -- chapter 2 The relationship between incentive, personality type and improvement in performance of imbeciles 1 / Gordon Claridge Neil O$1 (BConnor -- s chapter 3 Sedation threshold, personality, and the theory of neurosis / Gordon Claridge Captain Reg N. Herrington -- chapter 4 Why drug effects vary / Gordon Claridge -- chapter 5 The relative influence of weight and of (3z(Bnervous type(3y (Bon the tolerance of amylobarbitone sodium /s Gordon Claridge -- chapter 6 Animal models of schizophrenia -- The case for LSD-25 / Gordon Claridge -- chapter 7 Covariation between two-flash threshold and skin conductance level in first-breakdown schizophrenics -- Relationships in drug-free patients and effects of treatment / Gordon Claridge Kenneth Clark -- chapter 8 LSD -- A missed opportunity? / Gordon Claridge -- chapter 9 The schizophrenias as nervous types / Gordon Claridge -- chapter 10 Theoretical background and issues / Gordon Claridge -- t
Keywords: Difference (Psychology); Mental illness; Personality disorders; Psychology, Pathological; Temperament